Determinants of drug survival for etanercept in a long‐term daily practice cohort of patients with psoriasis. (February 2014) - van den, J.M.P.A.; van, P.P.M.; Driessen, R.J.B.; van de, P.C.M.; Seyger, M.M.B.; Kievit, W.; de, E.M.G.J.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Etanercept has proven to be effective and well tolerated in patients with psoriasis in several randomized controlled trials. What does this study add? This is the first daily practice study calculating drug survival rates of patients treated with etanercept for a maximum observation period of 7·5 years. Determinants of longer drug survival were calculated for general drug survival, and separately for discontinuation due to adverse events or ineffectiveness of therapy.